Contact Zone in TESOL: East and West Immersion - Min, Young-Kyung (Journal of International Students, 2012)
I was invited to give a talk at the Gwangju International Center (GIC) in Korea in Summer 2011. The GIC was established in 1999 by the Gwangju Citizens' Alliance to promote intercultural understanding and cooperation between foreign residents and local people in Gwangju, the capital of Chonnam Province, in Korea. Under the title of “Images of Writing across Cultures,” I gave my talk about culturally embedded writing practices across nations and presented some practical strategies that the audience could use in various writing contexts. There were about 60 people in the audience. Half of them were Korean and the other half were expatriates, which included high school students, teachers in private language institutes, K-12 schools, colleges and universities, house wives, retired professors, and publishers